Editorial: Introductions All Around - Editorial Board; Ian Beilin; Ellie Collier; Erin Dorney; Bethany Messersmith; Annie Pho; Ryan Randall; Cecily Walker (In the Library with the Lead Pipe, 2015)
In Brief: Over the past year, the Editorial Board has experienced some changes (yay, growing pains!). In this group post, current board members introduce themselves and talk about the types of articles they’d love to see submitted in 2016. We also thank all of our emeritus board members for their hard work shaping In The […]